IMPLEMENTASI BIMBINGAN DAN KONSELING IMPACT ISLAMI PADA SISWA SMK 1 KARANGANYAR PURBALINGGA - Helmi Abu Najah (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2019)
Abstract This study aims to determine the implementation of Islamic impact guidance and counseling in guidance and counseling services. The method used uses a qualitative approach. The data processed is the result of observations and interviews with students, teachers and principals. This has implications for the importance of using a variety of creative techniques and the use of media in counseling. The guidance and counseling services provided are not boring guidance and counseling services. The provision of services and Islamic impact counseling compel counselors to be creative and increase knowledge, especially for Islamic values. The results of this study describe the implementation of Islamic impact guidance and counseling in detailed guidance and counseling services to students of Vocational High School (SMK) N 1 Karanganyar Purbalingga. Keywords: implementation, Impact Islamic guidance counseling.